Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acs.inorgchem.0c02555
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning from Intraligand π,π* to Charge-Transfer Excited States Using Thiophene-Based Donor–Acceptor Systems

Abstract: A series of electron donor–acceptor compounds are reported in which both the donor and acceptor strengths are systematically altered using mono-, bi-, and terthiophene as donors and benzo­[c]­[1,2,5]­thiadiazole (btd), dipyrido­[3,2-a:2′,3′-c]­phenazine (dppz), and the corresponding rhenium­(I) complex, [ReCl­(CO)3(dppz)], as acceptors. The electronic properties of the compounds are characterized using electrochemistry, electronic absorbance and emission spectroscopies, and transient absorption spectroscopy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 82 publications
(149 reference statements)
0
10
0
Order By: Relevance
“…As would be expected, the intensity of the ICT band relative to the π‐π* band is proportional to the electron donating capabilities of the aryl substituent (Figure 3). [27] A summary of the absorption data between both the higher and lower energy bands and the emissions are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…As would be expected, the intensity of the ICT band relative to the π‐π* band is proportional to the electron donating capabilities of the aryl substituent (Figure 3). [27] A summary of the absorption data between both the higher and lower energy bands and the emissions are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…32 Gordon and co-workers have recently reported on a series of tricarbonyl Re(I) complexes with thiophenebased donor-acceptor systems with varying degrees of ILCT and localised π, π* characters. 33 They have also reported on a series of Pt(II) bis(acetylide) and Re(I) tricarbonyl complexes with triphenylamine-substituted phenanthroline ligands, in which the MLCT and ILCT characters were switched as a function of the substituents on the triphenylamine group. 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Gordon and co-workers have recently reported on a series of tricarbonyl Re( i ) complexes with thiophene-based donor–acceptor systems with varying degrees of ILCT and localised π,π* characters. 38 They have also reported on a series of Pt( ii ) bis(acetylide) and Re( i ) tricarbonyl complexes with triphenylamine-substituted phenanthroline ligands, in which the MLCT and ILCT characters were switched as a function of substituents on the triphenylamine group. 39 Further reports from the Gordon group on [Ru(N∩N) 3 ] 2+ complexes with N∩N ligands derived from substituted 1,10-phenanthroline showed that appending aromatic groups to the ligand changes the character from MLCT to a ligand-centred triplet ( 3 LC).…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37] Gordon and co-workers have recently reported on a series of tricarbonyl Re(I) complexes with thiophenebased donor-acceptor systems with varying degrees of ILCT and localised π, π* characters. 38 They have also reported on a series of Pt(II) bis(acetylide) and Re(I) tricarbonyl complexes with triphenylamine-substituted phenanthroline ligands, in which the MLCT and ILCT characters were switched as a function of the substituents on the triphenylamine group. 39 .…”
mentioning
confidence: 99%